Kebijakan Pendidik Dan Tenaga Kependidikan MI Kantor Kementerian Agama Kabupaten Aceh Tenggara - Muhammad Idris Maas Zaid; Saleh Adri; Harli Harli (Pusdikra-Publishing.com, 2022)
This study aims to describe how the policies of the Ministry of Religion of Islam in Southeast Aceh towards educators and education staff. This research uses descriptive qualitative. The research was conducted at the Office of the Ministry of Religious Affairs in Southeast Aceh. The data collection technique begins with presenting the data obtained in the field. After that, data reduction, namely selecting and sorting the required data, then followed by verification, namely the conclusion of data according to the problem under study. Based on the results of this study, it shows that the policies of educators and education staff, the Office of the Ministry of Religion of Islam in Southeast Aceh, found that the government's policies towards educators and education staff regarding the basic competencies of educators and education staff, teacher education, class rank of teachers and policies, the Office of the Ministry of Religion, Aceh Tenggara Dalam towards educators and educational staff.